2020
DOI: 10.15587/1729-4061.2020.198371
|View full text |Cite
|
Sign up to set email alerts
|

Control of a high-voltage discharge-pulse installation when implementing technological modes of an electrochemical explosion

Abstract: 29the treated object include the pressure waves and hydraulic flows of liquid that propagate throughout a working environment, which are used for destruction, shape-formation, crushing, dispersing, etc. [1].Most high-voltage discharge-pulse installations used in various technologies employ a capacitive drive as an energy source as part of a pulse current generator (PCG). When it is discharged to the intra-electrode gap, an expanding plasma channel is formed in a condensed environment, generating a Introduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
0
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
1
0
0
4
Order By: Relevance
“…Given the pulsed nature of the applied load, it should be assumed that the growth rate of these cracks is quite high; for example, the recorded rate of crack growth during the explosive destruction of diamonds was 7000 m/s. The studies of fine grinding of ores by electric discharges showed a high selectivity of the process, confirming the above assumption [45][46][47][48].…”
Section: Introductionsupporting
confidence: 72%
“…Given the pulsed nature of the applied load, it should be assumed that the growth rate of these cracks is quite high; for example, the recorded rate of crack growth during the explosive destruction of diamonds was 7000 m/s. The studies of fine grinding of ores by electric discharges showed a high selectivity of the process, confirming the above assumption [45][46][47][48].…”
Section: Introductionsupporting
confidence: 72%
“…В Институте импульсных процессов и технологий Украины на основе проведенных экспериментальных и теоретических исследований установлены основные закономерности ВЭХВ, его энергетические, гидродинамические и электрофизические характеристики, разработаны алгоритмы расчета параметров комбинированных энергоисточников на основе ВЭХВ, которые обеспечивают максимальное выделение химической энергии в канале разряда [5][6][7][8][9].…”
Section: высокопроизводительныеunclassified
“…При W Э = 450 Дж максимум J(G) наблюдается при G = 0,3⋅10 -3 кг; при этом w Э = W Э /G = 450/0,3×10 -3 = 1,5×10 6 Дж/кг.…”
Section: высокопроизводительныеunclassified
See 2 more Smart Citations